A Simple and Reproducible Stereomicroscopic Method to Assess Fungal Biofilms: Application to Antifungal Susceptibility Testing - Zinnat Shahina; Tanya Dahms (Bio-Protocol, 2023)
Candida albicans, a well-known opportunistic pathogen, is a major cause of human fungal infections. Biofilm formation is considered an important pathogenesis factor. Biofilms are less sensitive to antibiotics and immune responses, allowing them to colonize and persist in host niches. Biofilm screening is important in the identification of anti-biofilm drugs. However, developing nations, with limited financial resources, often do not have access to advanced scientific equipment. Here, we describe an in vitro, protocol using common materials and simple equipment to evaluate static microbial biofilms.